Star trek. The captains' summit [videorecording (Blu-Ray)] - Roddenberry, Gene; Shatner, William; Nimoy, Leonard; Kelley, DeForest, 1920-1999; Doohan, James; Takei, George, 1937-; Koenig, Walter, 1936-; Nichols, Nichelle (Paramount Home Entertainment, 2009)
William Shatner, Leonard Nimoy, Patrick Stewart, Johathan Frakes and host Whoopi Goldberg share insights, humorous moments, and intimate details about life on the set, working with each other, and how Star Trek has affected their lives.